Investigating the reason for high FF from ternary organic solar cells. (September 2021) - Li, Danqin; Zeng, Yihan; Chen, Zeng; Leng, Shifeng; Xiao, Zuo; Xue, Qifan; Hao, Tianyu; Lv, Meng; Wu, Hongbo; Lin, Lina; Yang, Jianming; Ma, Zaifei; et al.
Abstract: